Religious Moderation Character Education: A Strategy To Maintain Diversity And Indonesianness - Muhammad Iqbal, Lalu (Edukasi Islami: Jurnal Pendidikan Islam, 2023)
This article aims to explain the significance of religious moderation education in strengthening the character of national insight to maintain plurality in Indonesia. This article uses a qualitative approach by applying descriptive-analytical method, which is trying to critically describe the substance of various concepts and theories related to religious moderation. Data collection was analyzed using the content analysis method, namely by analyzing the meaning contained in the concept of religious moderation and how the concept is implemented in the life of Indonesian society. The concept of religious moderation is an approach in religious education that aims to produce individuals who are tolerant, able to dialogue, respect diversity, and able to maintain peace and security in a society of diverse beliefs.  It cannot be denied that religious extremism is often caused by an extreme mindset in understanding religious texts in a rigid, textual and scripturalist manner, without considering historical dynamics, social context, and maqashid in religion.